PARADIGM OPPOSITE OF NATURE OF ANCIENT GREEK POLIS (RECIPROCAL) AND ROMAN IMPERIAL (REDISTRIBUTIVE) TAX LAW - PATSURKIVSKYY, P.; HAVRYLYUK, R. (Ehrlich's Journal, 2023)
The article substantiates: the ancient Greek reciprocal (tax) law and the ancient Roman redistributive one are paradigmatic opposite phenomena. They have nothing in common but some external formal features. The ancient Greek reciprocal law was that of the citizens of the ancient Greek polises. The ancient Roman redistributive law was the law of the ancient Roman Empire as a substantial state. The most fundamental among the causes of paradigmatic distinction between the ancient Greek reciprocal law and the ancient Roman redistributive law became the late-Antique mental, in particular, and the worldview on the whole, revolution in the ancient Roman imperial society and its legal thinking compared to the ancient Greek polis mentality and consciousness. As a result of that revolution the ancient Greek polis tradition discontinued and the ancient Roman, imperical tradition arrived. It became one of the most fundamental milestones in the evolution of human societies, states and law. The idea, dominant till nowadays in the minds of the most scientists, of the organic unity and direct continuity of Hellenism and Romanizm, of the existence of a unified ancient civilization is not more than a myth, a methodological error. The roots of this myth dates back to great antiquity and are simultaneously (but at different times in varying proportions) both, the consequence of incredible complexities of the process of sociogenesis, politogenesis, genesis of the state, anthropogenesis, genesis of law and other, regular and random evolutionary changes, and ordinary human, including cognitive, errors, and to some extent the result of a profound, precily considered and handled in a masterly way disinformation. This myth is so enduring that even today it is still practically impossible to predict, more or less reasonably, the time of its collapse. By virtue of that, everybody has to consider it while seeking to cognize the Antiquity and, through it, to learn the modernity.